2005
DOI: 10.1029/2005eo090002
|View full text |Cite
|
Sign up to set email alerts
|

NASA supercomputer improves prospects for ocean climate research

Abstract: Estimates of ocean circulation constrained by in situ and remotely sensed observations have become routinely available during the past five years, and they are being applied to myriad scientific and operational problems [Stammer et al., 2002]. Under the Global Ocean Data Assimilation Experiment (GODAE), several regional and global estimates have evolved for applications in climate research, seasonal forecasting, naval operations, marine safety, fisheries, the offshore oil industry coastal management, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 14 publications
0
107
0
Order By: Relevance
“…Study of the present eddy-free motions on time scales of less than about 2 yr shows a strong coupling in both temperature and velocity between the upper and lower oceans, consistent with a primarily wind-forced response. Ponte (2012), using a different ECCO eddy-permitting state estimate (Menemenlis et al 2005), showed that abyssal noise could seriously compromise the interpretation of sea level variability and hence degrade the heat content estimates at the levels of accuracy needed here.…”
Section: Abyssal Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study of the present eddy-free motions on time scales of less than about 2 yr shows a strong coupling in both temperature and velocity between the upper and lower oceans, consistent with a primarily wind-forced response. Ponte (2012), using a different ECCO eddy-permitting state estimate (Menemenlis et al 2005), showed that abyssal noise could seriously compromise the interpretation of sea level variability and hence degrade the heat content estimates at the levels of accuracy needed here.…”
Section: Abyssal Signalsmentioning
confidence: 99%
“…For context, Fig. 9 is taken from the ECCO2, eddy-permitting state estimate of Menemenlis et al (2005), used by Ponte (2012), which shows that the eddy-noise variance (which is likely still underestimated owing to the 18-km horizontal resolution) is about 6 times larger than the background standard deviation. Also shown (Fig.…”
Section: A Variancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupled model is configured on a ''cubed-sphere'' grid encompassing the Arctic domain with open boundaries at around 558N in the Atlantic and Pacific sectors. Prescribed boundary conditions for potential temperature, salinity, flow, and sea surface elevation are provided from previous integrations of a global configuration of the same model [Menemenlis et al, 2005]. The sea ice component follows the viscous-plastic rheology formulation of Hibler [1979] with momentum Journal of Geophysical Research: Oceans…”
Section: A17 Model 18mentioning
confidence: 99%
“…The MITgcm configuration used covers a limited-area Arctic domain that has open boundaries at ;558 in the Atlantic and Pacific sectors. The exact boundary lines coincide with grid cells in a global cubic sphere MITgcm configuration (Menemenlis et al 2005;Fig. 2).…”
Section: A Model Descriptionmentioning
confidence: 99%